Carboxymethylcellulose/polyacrylic acid/starch-modified Fe3O4 interpenetrating magnetic nanocomposite hydrogel beads as pH-sensitive carrier for oral anticancer drug delivery system. (15th June 2021) - Mohammadi, Reza; Saboury, Ayda; Javanbakht, Siamak; Foroutan, Rauf; Shaabani, Ahmad
Graphical abstract: Highlights: CMC/PAA/St-Fe3 O4 interpenetrating magnetic hydrogel beads were successfully synthesized. 5-FU and DOX were individually loaded into the prepared nanocomposites. CMC/PAA/St-Fe3 O4 has a pH-responsive oral delivery property. Drug-loaded CMC/PAA/St-Fe3 O4 showed notable cytotoxicity toward SW480. Blank CMC/PAA/St-Fe3 O4 exhibited a cytocompatibility nature toward SW480. Abstract: Colon cancer is the most usual illness and its oral therapy is an important challenge owing to the serious side effects on the digestive system. For this aim, novel interpenetrating magnetic nanocomposite hydrogel beads were designed based on starch-modified Fe3 O4 NPs (St-Fe3 O4 ). Carboxymethylcellulose/polyacrylic acid/starch-modified Fe3 O4 ( CMC/PAA/St-Fe3 O4 ) beads were prepared via a simple method. The prepared materials were fully characterized using different analyses. Anticancer doxorubicin hydrochloride (DOX) and 5-fluorouracil (5-FU) were individually loaded into the prepared nanocomposites by immersing in the solution of drugs to investigate their productivity as the loading of different anticancer drugs. In-vitro drug delivery study was performed in mimicking the gastrointestinal tract (GIT) circumstances to demonstrate the efficiency of the prepared carrier as an oral delivery system (ODS). The drug release study revealed that CMC/PAA/St-Fe3 O4 nanocomposites could potentially prevent the release of 5-FU and DOX in the stomach acidic environment due to their pH-sensitive swelling manner, and also enhance the stability of drug dosing in the colorectal area. MTT assay showed significant cytotoxicity toward human colon cancer cell lines (SW480) for the drug-loaded nanocomposites; thus, they could potentially be administrated as an efficient carrier for anticancer ODS.